Developmental Ecological Psychology and a Coalition of Ecological–Relational Developmental Approaches. Issue 1 (2nd January 2018) - Szokolszky, Agnes; Read, Catherine
ABSTRACT: Developmental 1 Ecological Psychology began to conceptualize develop–ment in terms of the organism-environment system at a time when it was far from accepted to think about development in dynamic and systems terms. In this theoretical review, we argue that Developmental Ecological Psychology, based on mutualist ecological realism, has much to give to and to gain from other approaches to development that aim at building a developmental science on ecological–relational foundations. However, in order to exert greater influence, Developmental Ecological Psychology should pay attention to organismic development in a wider sense and should provide comprehensive theorizing about development as an ongoing and extended life process in multiple contexts. We review the theoretical foundations and prominent research directions in Develop- mental Ecological Psychology, noting strengths as well as lacunae. Then we move on to review major approaches that are partners for Developmental Ecological Psychology in a currently forming "coalition" of ecological–relational developmental science. In particular, we align the contributions of biologically rooted developmental systems approaches, dynamic systems approaches, phenomenologically rooted approaches, and sociocultural approaches. We focus on common ground, affinities, and synergies among these approaches and with Developmental Ecological Psychology. Thus, we define Developmental Ecological Psychology as an evolving, open discipline, seeking and finding principled cross-fertilization with a broad array of other relevant streams of thought.